The essential of engineering education involving critical thinking and problems solving skills among mechanical engineer employees - Wan Omar Ali Saifuddin, Wan Ismail; Ireana Yusra, Abdul Fatah; Hamzah, N; Muhammad, A.K (2019)
Engineering Education is a course that emphasis on soft skills that are related to critical thinking and the ability in solving problems. Creative and Critical Thinking Skills (CCTS) is a type of skill that had introduced and strongly emphasized in the education system, starting from primary school. Recently, all the exam questions in primary, secondary schools and public universities oriented to the principle of Higher Order Thinking Skills (HOTS) in (RMK 11 - Transforming Education System). The objective of this education program is to produce students that are more competent in solving problems by applying effectively various forms of knowledge that had studied theoretically. This study aims to examine the extent to which the needs of elements of critical thinking and problem-solving skills to produce competitive engineers from industries point of view. Feedback from respondents was taken through quantitative methods using a set of questionnaires. A total of 300 respondents have participated in this study. The study is expected to be a guide for future mechanical engineers who would be involved by the requirements of the mainstream industry.